Molecular Characterization and Genomic Function of Grapevine Geminivirus A - Sun, Suwei; Hu, Ya; Jiang, Guangzhuang; Tian, Yimin; Ding, Ming; Yu, Cui; Zhou, Xueping; Qian, Yajuan (Frontiers in Microbiology, 2020)
A new grapevine geminivirus A (GGVA) isolate (named as GGVA-17YM1) and its associated defective genome (GGVA-D) were identified from a grapevine sample collected in Yuanmou, Yunnan province, using sRNA high throughput sequencing and traditional Sanger sequencing. To explore the pathogenicity of GGVA and GGVA-D, infectious clones of GGVA-17YM1 and GGVA-D-17YM1 were constructed. Infection assays indicated that Nicotiana benthamiana plants inoculated with GGVA alone or a combination of GGVA and GGVA-D exhibited upward curled apical leaves and dwarfism. Southern blotting and quantitative real-time polymerase chain reaction analysis revealed that GGVA-D increased the accumulation level of GGVA DNA. Transient expression using a PVX-derived recombinant vector indicated that C2 and C4 encoded by GGVA are involved in symptom induction in N. benthamiana. Furthermore, the V2 protein inhibited local RNA silencing in co-infiltration assays in GFP transgenic N. benthamiana plants. Subsequently, full-length genome sequencing resulted in the identification of 11 different isolates of GGVA and 9 associated defective DNA molecules. Phylogenetic analysis based on whole genome sequences showed that all GGVA isolates, including our sequences, clustered into two distinct branches with no geographical grouping. Analyses of molecular variation indicated single nucleotide polymorphisms (SNPs) with more transitions (55.97%) than transversions (44.03%). Furthermore, the main variants for ORF C1, C3 or V1 were synonymous mutations, and nonsynonymous mutations for ORF C2, C4 and V2. Genetic selection analysis indicated that negative selection acted on four ORFs (V1, C1, C2 and C3), while V2 and C4 were under positive selection. Our results contribute to the characterization of the genetic diversity of GGVA and provide insights into its pathogenicity.